2004
DOI: 10.1002/humu.20086
|View full text |Cite
|
Sign up to set email alerts
|

The role of tau (MAPT) in frontotemporal dementia and related tauopathies

Abstract: Tau is a multifunctional protein that was originally identified as a microtubule-associated protein. In patients diagnosed with frontotemporal dementia and parkinsonism linked to chromosome 17, mutations in the gene encoding tau (MAPT) have been identified that disrupt the normal binding of tau to tubulin resulting in pathological deposits of hyperphosphorylated tau. Abnormal filamentous tau deposits have been reported as a pathological characteristic in several other neurodegenerative diseases, including fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
230
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(242 citation statements)
references
References 201 publications
(203 reference statements)
1
230
0
5
Order By: Relevance
“…Different mutations in this gene can cause progressive supranuclear palsy or frontotemporal dementia with parkinsonism, as well as other disorders. 91 Exposure to stress may differentially impact the function of brain-body pathways involved in regulating syndromal depression and anxiety, depending on an individual's level of BDNF (according to the presence of Met or Val alleles). Of course, this possibility needs to be examined in clinical samples, to determine if these pathways predict depression and anxiety at the level of disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Different mutations in this gene can cause progressive supranuclear palsy or frontotemporal dementia with parkinsonism, as well as other disorders. 91 Exposure to stress may differentially impact the function of brain-body pathways involved in regulating syndromal depression and anxiety, depending on an individual's level of BDNF (according to the presence of Met or Val alleles). Of course, this possibility needs to be examined in clinical samples, to determine if these pathways predict depression and anxiety at the level of disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, frontal and/or temporal brain regions are degenerated. Based on the variable presence and composition of pathologic brain inclusions, FTLD can be subdivided in three pathologic subtypes: FTLD with tau-positive brain deposits (FTLD-tau) [Rademakers et al, 2004], FTLD with tau-negative ubiquitin-positive inclusions (FTLDU), and FTLD without inclusions (dementia lacking distinctive histopathology [DLDH]). Positive family history is observed in up to 50% of FTLD patients Rosso et al, 2003] and most families are linked with a region at chromosome 17q21.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of these families, mutations were identified in the microtubule-associated protein tau gene (MAPT; MIM] 157140) [Hutton et al, 1998;Poorkaj et al, 1998]. MAPT mutations were strictly associated with FTLD-tau pathology [Rademakers et al, 2004]. Despite extensive mutation analyses of MAPT, chromosome 17q21-linked FTLD families with FTLDU pathology (FTLDU-17; MIM] 607485) did not segregate a MAPT mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, genetic studies have revealed that pathologically confirmed cases of PSP, CBD, and FTLD share mutations from a single gene (MAPT) [6,10,21,29,30,36]. Therefore, to encompass the whole spectrum of these disorders, an umbrella term called "Pick complex" has been proposed [17,20,26].…”
Section: Introductionmentioning
confidence: 99%